Why do companies engage in green marketing? Alternative green marketing strategies and the motivations for the green marketing approach - (:unkn) unknown (IGI Global, 2017)
In recent years, consumers and the business world have deemed environmental issues to be more important, and green marketing has become a competitive advantage involved in corporate strategies. This chapter aims to study the concept of green marketing in the business world. First, according to literature, evolving green marketing definitions are described in detail, and the importance of green marketing approach it assessed. Then, since green marketing approach must be integrated with corporate strategies, four green marketing strategic models are presented and discussed. The chapter concludes with a discussion of the implications for green marketing of motivating factors such as pressure from consumers, NGOs and environmental organizations, legislative authorities, cost and profit considerations and competition between companies. © 2017 by IGI Global. All rights reserved.